Impact of extreme hydrologic disturbance upon the sediment carbon quality in agriculturally impacted temperate streams. Issue 3 (18th June 2014) - Ford, William I.; Fox, James F.; Rowe, Harry
Abstract: The impact of extreme hydrologic disturbances on the quality of fine particulate organic carbon (FPOC) associated with sediments in low‐gradient, agriculturally impacted streams remains poorly understood despite the significance of the FPOC pool to benthic food webs, organic matter budgets and nutrient cycles. We estimated immediate and long‐term impacts of an extreme flow disturbance on FPOC quality using a 5‐year dataset of the stable carbon isotopic signature and a new metric for carbon quality. Results of the study show that the stable isotopic signature of sediment carbon is significantly enriched in the year following the extreme event, which reflects the streams response to accrual of degraded soil carbon. Further, our FPOC metric was found to be inversely proportional to the isotopic signature, suggesting an immediate shift of the benthic ecosystem to lower quality carbon that is retained for more than 1 year before recovering to the pre‐disturbance state. Following recovery, results show that the benthic ecosystem exports FPOC with quality that oscillates seasonally – the lowest quality observed in late spring and the highest quality in late fall. Although studies have addressed the response of high‐quality algal biomass to fluvial shearing, this study is the first to assess the response of high‐quality FPOC to an extreme hydrologic disturbance characterized by sediment deposition in an agriculturally impacted stream. Copyright © 2014 John Wiley & Sons, Ltd.